Archäologische Untersuchungen Über Temporalität und Dinge - Stabrey, Undine (Histoire, 2017)
How does time figure in archeology? This volume shows how the past can emerge as history and the reason why a part of human history was temporalized into a Stone Age, Bronze Age, and Iron Age.